Exploring family educational involvement and social skills in Chinese preschoolers: The moderating role of parent-child relationship - Liu, Hao; Qiu, Yuxi; Luo, Li (Frontiers in Psychology, 2022)
The purpose of this study was to examine parent-child relationship as a moderator of the association between family educational involvement and the social skills of preschoolers. A total of 4,938 children (M = 5.09-years-old, SD = 0.81) were sampled from 18 preschools in Hebei province, China, and their parents completed a survey packet to collect demographic information, as well as ratings of parental involvement, relationships with their children, and child social skill development. The results of multivariate regression analysis suggested that: (1) both home-based involvement and home-school conferencing could significantly predict preschoolers’ social skills, (2) there was stronger evidence for a relationship of home-based involvement and preschoolers’ social skills, (3) closeness in parent-child relationship moderated the path from home-based involvement to preschoolers’ social skills, and (4) there was no interactive effect between family educational involvement and parent-child conflict. These findings highlight the significance of the joint influences of family educational involvement and parent-child relationship in shaping children’s social skills. The impact of home-based involvement was boosted in the context of a close parent-child relationship.